Aluminium Metal Matrix Composite with Rice Husk as Reinforcement: A Review. (2018) - Yadav, Ajay Kumar; Pandey, Krishna Murari; Dey, Abhijit
Abstract: Aluminium metal matrix composite is a new generation material that have a potential to satisfying the recent demand of advance engineering technology. They are widely used in automobile industries, aerospace industries and many other like defence and marine systems. In composite material we achieve tailor properties of material which fulfil our recent demand. Researchers have been observe that addition of rice husk ash in aluminium alloy matrix yields better mechanical and physical properties and high wear rate resistance of composite. The scanning electron micrographs of composite showed that rice husk ash is distributed homogeneously throughout the aluminium matrix. At high temperature wear of aluminium alloy changes from micro cutting to oxidation wear. Due to difference in the coefficient of thermal expansion between matrix material and reinforcement material strain fields created and wear resistance of composite material is improved. In this paper review we focus on the fabrication method and wear resistance of Al alloy/rice husk ash composite material.